The Right to be Forgotten: Emerging Legal Issues - Kiriiak, Oksana Vasylivna (Review of European and Comparative Law, 2021)
This paper contextualizes and analyzes the main emerging approaches to the understanding of the right to be forgotten and its application in praxis, using legislation and judicial practice of the European Union and Ukraine as reference scales. By bridging the gap between positive and interpretative orders of law implementation, which were previously imperatively opposed and considered mutually exclusive in the Ukrainian legal system, the paper supports the arguments that the process of mastering the protection of right to be forgotten requires a further mindset shift equally for-Internet providers and all involved law enforcers.